Externalization Of Tacit Knowledge Implies A Simplified Theory of Cognition - Virtanen, Ilkka (Journal of Knowledge Management Practice, 2011)
Externalization of tacit knowledge has been on the focus of both humancentric and ICT-centric knowledge management theory for over fifteen years. The whole conception of tacit knowledge in the knowledge management literature has been criticised of being based on incorrect interpretation of Polanyi’s original theory of knowledge. At the same time, it has been reported that many knowledge management projects related to externalization of tacit knowledge do not meet their objectives. The above-mentioned findings suggest that there is something wrong in the dominant epistemology of knowledge management theory. We analyzed the conception of externalization of tacit knowledge from the perspectives of epistemology and theory of cognition. We identified various problems related to the dominant conception of mind in the knowledge management literature. We argue that the conception of externalization of tacit knowledge is based on the simplified view on human mind, which also questions the idea of management of tacit knowledge.